2001
DOI: 10.1143/jjap.40.l721
|View full text |Cite
|
Sign up to set email alerts
|

Memory Operation of Silicon Quantum-Dot Floating-Gate Metal-Oxide-Semiconductor Field-Effect Transistors

Abstract: The drain current versus gate voltage characteristics of metal-oxide-semiconductor field-effect transistors (MOSFETs) with a silicon quantum-dot (QD) layer floating gate have shown the unique hysteresis and current bumps which arise from the electron charging or discharging of the QDs with an average dot height of 5 nm. The drain current response to application of a single-pulse gate bias has revealed that the multiple-step charging of the QD layer occurs until single electron occupation at each QD is achieved. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 7 publications
2
55
0
Order By: Relevance
“…We have fabricated n-MOSFETs with a doubly-stacked Si-QDs floating gate [6,7], and confirmed the multi-step electron charging to the Si-QDs floating gate associated with Coulomb blockade effect from distinct bumps in drain current-gate voltage characteristics observed in ramping up the gate voltage after complete discharging at room temperature. We have also found that, in the temporal change in the drain current at a constant gate bias, Id-t, the electron injection to the Si-QDs floating gate proceeds in a stepwise fashion through metastable states with a fairly long incubation period to the next charging as seen in Fig.…”
Section: Characterization Of Multi-step Charging To Si-qds Floating Gsupporting
confidence: 52%
See 2 more Smart Citations
“…We have fabricated n-MOSFETs with a doubly-stacked Si-QDs floating gate [6,7], and confirmed the multi-step electron charging to the Si-QDs floating gate associated with Coulomb blockade effect from distinct bumps in drain current-gate voltage characteristics observed in ramping up the gate voltage after complete discharging at room temperature. We have also found that, in the temporal change in the drain current at a constant gate bias, Id-t, the electron injection to the Si-QDs floating gate proceeds in a stepwise fashion through metastable states with a fairly long incubation period to the next charging as seen in Fig.…”
Section: Characterization Of Multi-step Charging To Si-qds Floating Gsupporting
confidence: 52%
“…So far, we have reported spontaneous formation of Si-QDs on thermally-grown SiO 2 with a fairly uniform size distribution and a high areal density (N10 11 cm − 2 ) by controlling the early stages of LPCVD from SiH 4 [5], and demonstrated unique multiple-step electron charging in the Si-QDs floating gate even at room temperature [6,7]. For precise control of the multi-valued memory operation, a clear insight into the charging and discharging characteristics of the Si-QDs is imperative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The use of floating gate composed of discrete nanodots reduces the problems of charge loss encountered in conventional plate-type flash memories, allowing further scaling of tunnel oxide and smaller operating voltages, better endurance, and fast write/erase speeds. 1,2 The discrete charge storage elements utilized in such devices are usually isolated silicon or germanium nanocrystals fabricated by chemical vapor deposition, [1][2][3][4] low energy ion implantation, 5,6 annealing of silicon rich oxide, 7 thermal oxidation of SiGe, 8 aerosol nanocrystal formation, 9 traps in nitride film, 10 or self-assembled metal nanoparticles. 11 The performance and the success of floating nanodot gate memories strongly depend on the structural characteristics of fabricated nanodots such as size, shape, and in-plane ordering and density of them in the MOS stacked structure.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete charged states of Si quantum dots (Si-QDs) originating from quantization and charging effects have motivated us to apply the Si-QDs to charge storage nodes for floating gate MOS memories [1][2][3][4][5]. Previously, we have reported the self-assembling formation of the Si-QDs from chemical vapor deposition (LPCVD) of pure SiH 4 [6] and demonstrated that, using an atomic force microscopy (AFM)/Kelvin force microscopy (KFM) technique [7][8][9], the amount of charges stored in each Si-QD can be evaluated from the surface potential change due to electron injection to and extraction from the Si-QDs [10].…”
Section: Introductionmentioning
confidence: 99%